Influencing Factors for Intention to Reusing Delivery Box Packaging of Consumers in Thailand - Samerjai, Chattayaporn; Sartmoon, Soibubpha; Sukhaparamate, Supawat (Journal of Humanities and Social Sciences Thonburi University, 2021)
The objective of this research was to study the factors affecting intention to reusing delivery box packaging of consumers in Thailand. A questionnaire was used to collect data online from 336 samples by Stratified Random Sampling, classified by the location of the target. The Structural Equation Model (SEM) technique was applied to analyze the data. The research results were found that: 1) awareness of consequence, perceived behavior control, and moral norm had positively influenced usage intention. The most affecting factor to usage intention was convenience, 2) usage intention and convenience affected actual usage behavior of the consumers, respectively, 3) convenience and perceived behavior control influenced usage intention at very high level. 4) subjective norm influenced usage intention through moral norm.